The effect of water currents on post-smolt Atlantic salmon, Salmo salar (L.). A welfare approach to exposed aquaculture - Solstorm, Frida (Aquaculture, 2017)
The future development of Atlantic salmon (Salmo salar L.) aquaculture is limited by the availability of space and suitable environments along coastal areas. Utilising exposed areas is a possible solution to this problem. The technology for offshore and exposed aquaculture is well developed, but there is a lack of knowledge concerning the effect of fast water current velocities on fish. In some locations, velocities exceed what is considered the critical swimming speed for salmon. Exposing salmon to such fast currents could severely compromise their welfare. Therefore, it is of utmost importance to evaluate the effects of strong water currents on individual fish. As a first approach, field observations were conducted at an exposed site where salmon behaviour was monitored in relation to current velocity. A behavioural adaptation to fast currents was observed at an ambient current velocity of approximately 0.7 BL s-1. At this velocity, some fish broke their circular schooling behaviour and maintained position against the current, creating a mix of swimming behaviours, i.e., both circular and standing on the current. Further increases in velocity (0.9 BL s-1) resulted in all fish abandoning the circular swimming behaviour to stand on the current. To explore the effect of a single parameter, water current velocity, a six-week laboratory experiment was conducted. Atlantic salmon post-smolt were exposed to three different velocities in raceways; slow (0.2 BL s-1), moderate (0.8 BL s-1) and fast (1.5 BL s-1). The setup forced the fish to primarily swim at the prevailing velocity. Fish growth, muscle composition and blood chemistry were analysed before and after the experiment. All fish were also examined for fin erosions, external injuries, skeletal morphology and bone composition. The fish behaviour was studied in detail throughout the experiment. The setup did not allow for circular swimming behaviour, as can be observed in sea cages. However, the plasticity of salmon behaviour was also clear in this setup, and the ...